Avaliação de metodologia de preparo de amostra de petróleo por digestão ácida auxiliada por microondas para determinação de metais por ICP-OES - Silva, Izabel Kaline Vicente da (2012)
This project describes a methodology optimization that would allow for a more efficient microwave assisted digestion process for petroleum samples. With the possible chance to vary various factors at once to see if any one factor was significant enough in the answers, experimental planning was used. Microwave assisted digestion allows, through the application of potency, an increasing number of collisions between the HNO3 and H2O2 molecules, favoring sample opening for complex matrixes. For this, a 24 factorial experimental planning was used, varying potency, time and the volumes for HNO3 65% and H2O2 30%. To achieve the desired answers, several elements were monitored (C, Cu, Cr, Fe, Ni, Zn and V) through Inductively coupled plasma atomic emission spectroscopy (ICP-OES). With this initial study it was noticed that the HNO3 was not a significant factor for any of the statistical studies for any of the analytes and the other 3 factors and their interactions showed statistical significance. A Box Behnken experimental planning was used taking in consideration 3 factors: H2O2 volume, time (min) and Potency (W), Nitric Acid kept at 4mL for a mass of 0,1g of petroleum. The results were extremely satisfying showing higher efficiency in the digestion process and taking in a responsibility between the answers for each analyte and the carbon monitoring was achieved in the following conditions: 7mL of H2O2, 700 Watts of potency and a reaction time of 7 minutes with 4mL de HNO3 for a mass of 0,1g of petroleum. The optimized digestion process was applied to four different petroleum samples and the analytes determined by ICP-OES